PREFERENSI PRIORITAS PENGEMBANGAN RUANG PADA PERUMAHAN TIPE 21 - Annisa Oktareangga Dheany; Preambudi, Akbar (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
Type-21 houses are among the most popular forms of housing for low-income communities due to their affordability and the support of government subsidy programs. However, the limited building area encourages occupants to undertake spatial transformations to meet functional needs and accommodate the dynamics of domestic activities. This study aims to identify the preferences and priorities of spatial development in Type-21 housing as a basis for understanding residents’ adaptive spatial patterns. Data were collected through questionnaires, interviews, and field observations involving 24 Type-21 houses located in four residential areas in Magelang. Samples were selected purposively, focusing on privately owned houses that had undergone renovation. The analysis was conducted by assigning scores to the sequence of space priorities based on interview results and observations of layout changes at each renovation stage. The findings reveal that the top three space priorities are the living room, master bedroom, and main bathroom/WC, which represent the basic functions originally provided by developers. However, the kitchen emerged as an additional primary need, considered essential by all respondents. Subsequent priorities include the terrace, additional bedrooms, and laundry areas, which develop according to the economic capacity and family size of each household. These results indicate that spatial development in small-scale housing occurs progressively and adaptively,